Impacts of globalization in the decision making process of agricultural enterprises - Fehér, István; Mihály, Nikolett (Studia Mundi – Economica, 2017)
The study focuses on the impacts of globalization on the decision making process of choosing seeds in some of the Hungarian agricultural enterprises. First of all, we analyze the objective effects and their general consequences in the Hungarian agricultural sector. Then we concentrate on the typical “heuristics” in the decision making process when the owners choose seed products. Heuristics are used when people are in uncertain situations and they judge probability and frequency.